The biosynthetic pathway of asparagine-linked oligosaccharides of glycoproteins - Staneloni, Roberto J. (1979)
A dolichyl diphosphate oligosaccharide containing glucose, mannose and N-acetylglucosamine is the precursor of the sugar -moiety of some glycoproteins. Studies of glycoproteins produced by virus-infected cells, using endo-N-acetylglycosaminidase for the liberation of the sugar moiety, have shown that the glucose-containing oligosaccharide is transferred to protein, then the glucose and some mannose residues are removed and acetlyglucosamine, galactose and sialic acid are added.